World food markets into the 21st century: environmental and resource constraints and policies - Rosegrant, Mark W.; Ringler, Claudia (Wiley, 1997)
The article reviews and synthesizes the evidence on biophysical limits to crop productivity; plant genetic resources and biotechnology; the availability of plant nutrients; soil and land degradation; the increasing scarcity and declining quality of water; and the impact of global climate change on agriculture.